SP-A and SP-D surfactant proteins and conventional risk factors for chronic non-infectious human diseases - K. Yu. Nikolaev; O. S. Kharlamova; I. A. Kosarev; N. F. Dadashova; Ya. K. Lapitskaya (Сибирский научный медицинский журнал, 2023)
Surfactant proteins SP-A and SP-D, which belong to the family of collagen-containing type C lectins, are used as diagnostic and prognostic markers for many acute and chronic respiratory diseases. The aim of the study is to assess the impact of conventional risk factors for chronic non-infectious diseases on SP-A and SP-D protein levels by means of systemic and structural analysis on the basis of relevant publications from international databases and official WHO reports. This analytical review concludes that widespread expression of SP-A and SP-D is documented in numerous studies, and, although the lungs remain the main site of synthesis of surfactant proteins, one can expect its significant impact on the immune and inflammatory response in many organs and tissues. The authors note that there are several known extrapulmonary effects of these proteins. However, many mechanisms of additional cellular effects of SP-A and SP-D outside the bronchopulmonary system still remain unstudied, which indicates the prospects for further research in this area.